P50 Students as educators: developing your future simulation faculty. (5th November 2017) - Sivakumar, C; Taylor, S; Campbell, A; Gopal, A
Abstract : Background: Student ASPiH (sASPiH) is the special interest group for students and early postgraduates within the Association for Simulated Practice in Healthcare (ASPiH). sASPiH aims to recruit, retain and develop undergraduate healthcare professionals within ASPiH. Our platform for innovation model has been implemented, and focuses on development of our members nationally. Our primary focus is to support students by providing online and face-to-face educational opportunities/resources or highlighting opportunities of professional value in simulation and technology-enhanced learning. These can be both internal and external to sASPiH; the latter of which is the focus of this work. Project Aims: Our current drive is expansion; how do we encourage more students to get involved with simulation? We intend to encourage and support institutions (i.e., simulation centres) to involve students in the design and provision of simulation, helping them work together in a meaningful way for both sides. There are many models of successful engagement throughout the country to draw on; student selected component modules within undergraduate curriculum1; student societies dedicated to, or with interests in, simulation; or even establishing a rigorous educational programme of learning to complete2. Intended Outcomes: Using these case studies and qualitatively analysing the experiences of those involved, we intend to disseminate our findings and encourage the establishment of bespoke initiatives across the country in co-operation with local centres and students. This could be as simple as a sASPiH representative at each medical school as a point of contact; running regional and national workshops; or even supporting motivated individuals by providing access to expertise, contacts or mentorship within ASPiH. There is no "one-size-fits-all" method, and we acknowledge and welcome this; bespoke solutions are needed, fitted to available resources and local appetite. Conclusion: By providing exciting and innovative opportunities to promote involvement in simulation design and provision amongst undergraduates, sASPiH wishes to help develop the healthcare simulation practitioners of the future. This is with the intention of allowing them to develop earlier in a way that benefits both institute and individual, increasing the likelihood of retention and continued engagement as local faculty as they progress from their junior stage.